Limited role of children in transmission of SARS‐CoV‐2 virus in households—Immunological analysis of 26 familial clusters. Issue 1 (27th January 2023) - Sieber, Justyna; Schmidthaler, Klara; Kopanja, Sonja; Weseslindtner, Lukas; Stiasny, Karin; Götzinger, Florian; Graf, Alexandra; Krotka, Pavla; Hoz, Jakub; Schoof, Anja; Dwivedi, Varsha; Frischer, Thomas; et al.
Abstract: Background: The impact of children on the transmission of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) remains uncertain. This study provides an insight into distinct patterns of SARS‐CoV‐2 household transmission in case of pediatric and adult index cases as well as age‐dependent susceptibility to SARS‐CoV‐2 infection. Methods: Immune analysis, medical interviewing, and contact tracing of 26 families with confirmed SARS‐CoV‐2 infection cases have been conducted. Blood samples were analyzed serologically with the use of a SARS‐CoV‐2‐specific IgG assay and virus neutralization test (VNT). Uni‐ and multivariable linear regression and mixed effect logistic regression models were used to describe potential risk factors for higher contagiousness and susceptibility to SARS‐CoV‐2 infection. Results: SARS‐CoV‐2 infection could be confirmed in 67 of 124 family members. Fourteen children and 11 adults could be defined as index cases in their households. Forty of 82 exposed family members were defined as secondarily infected. The mean secondary attack rate in households was 0.48 and was significantly higher in households with adult than with pediatric index cases (0.85 vs 0.19; p  < 0.0001). The age (grouped into child and adult) of index case, severity of disease, and occurrence of lower respiratory symptoms in index cases were significantly associated with secondary transmission rates in households. Children seem to be equally susceptible to acquire a SARS‐CoV‐2 infection as adults, but they suffer milder courses of the disease or remain asymptomatic. Conclusion: SARS‐CoV‐2 transmission from infected children to other household members occurred rarely in the first wave of the pandemic, despite close physical contact and the lack of hygienic measures. Abstract :